i-Campus: towards the information integration for UiTM Perak Branch implementation of smart campus / Muhd Shufi Aiman Muhd Shuhaimi and Izham Ghani - Muhd Shuhaimi, Muhd Shufi Aiman; Ghani, Izham (2024)
As a result of the fast advancement of science and technology, the i-Campus initiative integrates information and communication technology (ICT) and the Internet of Things (IoT) into a traditional campus, transforming it into a smart campus. This concept aligns with the development of smart cities and aims to provide a modern and connected environment for learning, efficient administrative operations, and enhanced collaboration within the university community. This paper utilizes qualitative interviews with experts to achieve the research objective of improving the learning and teaching experience, streamlining administrative processes, and exploring the collaborative features and tools available within smart campus.